Composition and Abundance of Periphyton Types in Artificial Habitat with Different Attractor Media in the Koto Panjang Reservoir Kampar Regency - Dimas Dwi Nugroho Santoso; Budijono Budijono; Asmika Harnalin Simarmata (Jurnal Perikanan dan Kelautan, 2024)
An artificial habitat comprises a series of structures or attractor media as a habitat for aquatic biota in the waters. This study aims to determine the best attractor media viewed from the abundance of periphyton found in artificial habitats. This research was conducted in July - August 2023 using the experimental method. Periphyton sampling was done four times with an interval of one week and then identified based on the reference identification book. Water quality parameters measured were temperature, brightness, pH, Dissolved Oxygen, nitrate, and phosphate. The data obtained were statistically analyzed using a two-way ANOVA and BNt tests in MS. Excel 2020. The results showed that there were 17 species of periphyton found, consisting of 5 classes, namely Bacillariophyceae (8 species), Zygnematophyceae (4 species), Chlorophyceae (3 species), Cyanophyceae (1 species), and Trebouxiophyceae (1 species). The total abundance of periphyton obtained ranged from 13.448 – 21.406 cells/cm2, and the highest is on plastic bottle attractors ranging from 3.232 – 8.318 cells/cm2. The type of periphyton found mostly was Navicula sp. (6.602 cells/cm2). Based on the periphyton abundance, it can be concluded that the best attractor for periphyton media is the used plastic bottle.